Implementation of causal control operators to detect distributed events (2016)
This paper discusses the design and implementation of three operators to control and predicate about causality relation between events in a distributed system. Concretely, we start from KETAL, a kernel conceived to detect patterns of distributed events, and we motivate the need to keep track of causality relations between events on m-health applications over Wireless Body Area Networks (WBAN). We then introduce a causal event model and we present a detailed implementation that allows the notion of causality in KETAL. This implementation is based on vectorial clocks, and it supports the detection of concurrent and causal relationships, plus the dynamic administration of the nodes involved in the system.